Science Commissioning of NIHTS: The Near-infrared High Throughput Spectrograph on the Lowell Discovery Telescope. (17th March 2021) - Gustafsson, Annika; Moskovitz, Nicholas; Cushing, Michael C.; Bida, Thomas A.; Dunham, Edward W.; Roe, Henry
Abstract: The Near-Infrared High Throughput Spectrograph (NIHTS) is in operation on the 4.3 m Lowell Discovery Telescope (LDT) in Happy Jack, AZ. NIHTS is a low-resolution spectrograph ( R ∼ 200) that operates from 0.86 to 2.45 microns. NIHTS is fed by a custom dichroic mirror which reflects near-infrared wavelengths to the spectrograph and transmits the visible to enable simultaneous imaging with the Large Monolithic Imager (LMI), an independent visible wavelength camera. The combination of premier tracking and acquisition capabilities of the LDT, a several arcminutes field of view on LMI, and high spectral throughput on NIHTS enables novel studies of a number of astrophysical and planetary objects including Kuiper Belt Objects, asteroids, comets, low mass stars, and exoplanet hosts stars. We present a summary of NIHTS operations, commissioning, data reduction procedures with two approaches for the correction of telluric absorption features, and an overview of select science cases that will be pursued by Lowell Observatory, Northern Arizona University, and LDT partners.